POMFRET FISHERY OF INDIA WITH SPECIAL REFERENCE TO THE CATCH STATISTICS OF MAHARASHTRA AND GUJARAT COASTS - Prasannakumari, B; Dharmaraja, S K (Indian Journal of Fisheries, 2011)
The pomfrets constitute about 2.32% of the total marine fish production in India. The bulk of the catch comes from Maharashtra and Gujarat States, which jointly contribute to about 61% of the total all India pomfret landings. The fishing season for pomfret fishery in the States of Maharashtra and Gujarat and the gears employed for the exploitation of the fishery in these States are given.